Professional Spirituality is the Basis of the Personal and Professional Development of the Future Teacher - Mutallibjonov Ma’rufjon (International Journal on Integrated Education, 2023)
This article provides information on the appropriate approaches to creative approaches to spiritual and educational activities for future teachers. It also reveals effective ways to form a system of spiritual and educational activities for future teachers.